Entre a escola pública e o ensino superior- a longa jornada dos jovens periféricos de Araçoiaba da Serra- SP - Lima, Larissa Corrêa de (Universidade Federal de São Carlos, 2021)
The present work reviews the history of formal education in Brazil, highlighting the main educational public policies, especially those that enable access to higher education by the popular class. As a result of globalization and the constant demands of the market, qualification at a higher level has become essential for social and/or economic ascension. in Brazilian higher education, namely PROUNI, FIES and ENEM. And finally, the possible obstacles that young people from peripheral schools face to join HEIs, whether public or private. For this, we sought to know the Bairro Jundiaquara State School, located in the municipality of Araçoiaba da Serra - SP, in order to verify how these phenomena reverberate in the peripheral school.
Between public school and higher education - the long journey of young people from the periphery of Araçoiaba da Serra- SP
Keywords: Educação; Escola pública; Políticas Públicas; Ensino superior; Education; Public school; Public policy; University education; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA